Russian Officers during the Years of Revolutionary Turmoil and the Civil War: Moral and Political Choice - Gennady Viktorovich Marchenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article reveals the reasons for the different moral and political choice of officers in favor of «reds» or «whites» during the revolution and the civil war. The dilemma of choice is examined on the basis of an appeal to the worldview of the pre-revolutionary officers of the Russian army and the moral content of officer traditions. Traces of the historical continuity of the education of patriotism and civic-mindedness are also analyzed.